2022
DOI: 10.3389/fphys.2021.801340
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Exosomes: Cross-Regulated Pathways Playing Major Roles in Hepatic Stellate Cells Activation and Liver Fibrosis

Abstract: Chronic liver injury, regardless of the underlying disease, results in gradual alteration of the physiological hepatic architecture and in excessive production of extracellular matrix, eventually leading to cirrhosis Liver cellular architecture consists of different cell populations, among which hepatic stellate cells (HSCs) have been found to play a major role in the fibrotic process. Under normal conditions, HSCs serve as the main storage site for vitamin A, however, pathological stimuli lead to their transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 135 publications
0
11
0
Order By: Relevance
“…Free fatty acids released by LD degradation are thought to be the energy sources for the fibrogenic response in HSCs. Blocking autophagy promoted lipid accumulation in HSCs with a quiescent phenotype, and attenuated liver fibrosis in vivo [ 41 ]. At present, no study has confirmed that huc-MSC-derived exosomes promote the deactivation of fibrogenic HSCs, which is related to autophagic regulation, but apparently more LDs accumulated in the cytoplasm of HSC-T6 cells in the HSTP1-Exos treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Free fatty acids released by LD degradation are thought to be the energy sources for the fibrogenic response in HSCs. Blocking autophagy promoted lipid accumulation in HSCs with a quiescent phenotype, and attenuated liver fibrosis in vivo [ 41 ]. At present, no study has confirmed that huc-MSC-derived exosomes promote the deactivation of fibrogenic HSCs, which is related to autophagic regulation, but apparently more LDs accumulated in the cytoplasm of HSC-T6 cells in the HSTP1-Exos treated group.…”
Section: Discussionmentioning
confidence: 99%
“…87 Numerous reports have demonstrated that HSC-derived exosomes actively participate in the pathological changes of various liver diseases, all of which are achieved by changes in the protein levels of key signaling pathway molecules. [88][89][90][91]…”
Section: Protein Metabolismmentioning
confidence: 99%
“…Autophagy plays a crucial role in hepatic homeostasis, and its deregulation is associated with liver diseases [25]. Studies have demonstrated that transformation of quiescent HSCs from the adipogenic to the myofibroblast profile, a hallmark in the propagation of hepatic fibrosis, is mediated through stress-induced autophagy [25,26]. We previously reported that heparanase promotes autophagy by suppressing, among other effects, mTORC1 activity [27][28][29].…”
Section: Discussionmentioning
confidence: 99%